Characterization of the secondary phases in spray formed Al–Zn–Mg–Cu–Sc–Zr alloy during hot compression. Issue 16 (24th June 2016) - Ning, Z.L.; Guo, S.; Zhang, M.X.; Cao, F.Y.; Jia, Y.D.; Sun, J.F.
Abstract: Abstract : An Al–10.83Zn–3.39Mg–1.22Cu–0.16Zr–0.16Sc alloy was produced using the spray deposition technology. The microstructure evolution within temperature ranging between 613 K and 733 K during hot pressing process at different initial strain rate was investigated in a transmission electron microscope (TEM). Partial resolution of the primary precipitates in the deposited microstructure, such as η-MgZn2 and Al3 (ScZr), took place. Moreover, new secondary η-MgZn2 and Al3 (ScZr) precipitated from the super saturated solid solution and their effects on the recrystallization were also analyzed. The Al3 (ScZr) and η-MgZn2 precipitation can act as barriers for the movement of both dislocations and grain boundaries, which are the main factors for hindering the recrystallization. Additionally, the dislocation slide during hot deformation was also investigated in detail. The spray deposition Al–Zn–Mg–Cu alloy own the well deformability, and the typical perfect dislocations can be found in the hot deformation Al–Zn–Mg–Cu alloy.